A Risk Factors and Prevention of Pressure Injuries After Orthopedic Procedures: A Literature Review - Zulfiqar, Zeeshan; Kot, Jakub; Zjawiony, Julia; Leja, Wiktoria; Latalska, Katarzyna; Błaszczak, Maciej; Szczupaj, Maciej; Pastuszak, Andżelika; Borkowski, Konrad; Rudnicki, Jakub (Quality in Sport, 2026)
Aim: The objective of this narrative review was to summarize existing literature on the epidemiology, mechanisms, risk factors and prevention of pressure injuries following orthopedic surgery. Materials and methods: A focused literature search was performed using recently published scientific literature related to pressure injuries, pressure ulcers, orthopedic surgery, fractures, hip fractures, perioperative care, device-associated injuries, nutrition, and early mobility. Results: Patients with orthopedic conditions have a greater chance of developing pressure ulcers due to their pain from fractures, limited mobility, being on transport surfaces or in the hospital for long periods, the way they are positioned during surgery, delayed post-op mobilization, and use of casts, braces, and/or splints or other orthopedic devices. The main risk factors are age, frailty, lack of nutrition, hypoalbuminemia, problems with circulation, prolonged surgical time, skin being too moist, and uses of devices over time. Conclusions: Pressure ulcers that occur after orthopedic surgery should be seen not just as complications of nursing care but also indicate a higher potential for issues related to perioperative care or quality of care. Prevention efforts to prevent pressure ulcers should start with patient admission to the hospital and continue through the time spent in surgery, rehabilitation, and discharge planning. A multi-disciplinary approach utilizing risk assessment, skin assessment, pressure relief, anticipating how to position the patient, nutrition, monitoring of the device used on the patient, and getting the patient out of bed as soon as possible post-operatively should help to decrease the potential for pressure ulcer development in orthopedic patients.